Ficus auriculata (fig) extracts induced cell cycle profile changes and apoptosis through caspase-independent pathway in human LungAdenocarcinoma cell line, A549 - Jamil, Elyna Fatini; Abdul Ghani, Radiah (Iranian Academic Center of Education, Culture and Research (A.C.E.C.R.), 2017)
Background: Ficus auriculata (fig) has immense value of benefits with regards to their medicinal and therapeutic properties. It has been long used in traditional folk medicine, and one of the fruits mentioned in Al-Quran. Many scientific researches have proven the usage of this natural medicine in in vitro and in vivo studies, where anti-cancer is among of its recognized properties. Objective: To acquire further details on how F. auriculata (fig) inhibited cancer growth, we investigated the effects of its exposure on cell cycle profile. Methods: Subsequently we determined the type of cell death and the mechanism it induced using flow cytometer. Human lung adenocarcinoma cell line A549 was selected as the model of this study. Results: It is indicated significant decreased of A549 cells in G0/G1and concurrent accumulation of cells in G2/M phase. Cell death analysis revealed significant late apoptosis induced by F. auriculata (fig) via caspase independent pathway. Conclusion: Therefore, we concluded that F. auriculata (fig) is one of the promising natural medicines that can be used as cancer preventive strategy, as a result from its effects against cell cycle profile and apoptosis via caspase independent pathway.